2019
DOI: 10.1002/ange.201814452
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Deaminative Functionalizations of Primary Amines by Photoinduced Single‐Electron Transfer

Abstract: The use of pyridinium-activated primary amines as photoactive functional groups for deaminative generation of alkylr adicals under catalyst-free conditions is described. By taking advantage of the visible light absorptivity of electron donor-acceptor complexes between Katritzkypyridinium salts and either Hantzsch ester or Et 3 N, photoinduced singleelectron transfer could be initiated in the absence of ap hotocatalyst. This general reactivity platform has been applied to deaminative alkylation (Giese), allylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 76 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Aggarwal and co-workers found that the 2,4,6-triphenylpyridinium moiety in 1 could also form the key EDAcomplex with Hantzsch ester 9,which upon photoexcitation functions as as ingle-electron reductant. [54] Thee nsuing pyridinium fragmentation liberates the desired alkyl radical, which was shown to efficiently undergo av ariety of transformations, including aGiese reaction with electron-deficient alkenes 10, as well as allylation with allyl sulfones 12 (Scheme 10). The…”
Section: N-carbon-substituted Pyridinium Reagentsmentioning
confidence: 99%
“…Aggarwal and co-workers found that the 2,4,6-triphenylpyridinium moiety in 1 could also form the key EDAcomplex with Hantzsch ester 9,which upon photoexcitation functions as as ingle-electron reductant. [54] Thee nsuing pyridinium fragmentation liberates the desired alkyl radical, which was shown to efficiently undergo av ariety of transformations, including aGiese reaction with electron-deficient alkenes 10, as well as allylation with allyl sulfones 12 (Scheme 10). The…”
Section: N-carbon-substituted Pyridinium Reagentsmentioning
confidence: 99%
“…Photoorganocatalysis is a low-cost and environmentally friendly alternative. [5,6] However, each of these catalysts has certain limitations. For example, benzophenones have a long-lived triplet state, which allows a hydrogen atom transfer (HAT) process to occur.…”
Section: Introductionmentioning
confidence: 99%
“…Later, methods without sacrificial reductant were also established, forming an EDA complex between the used substrates. Examples of this strategy are borylations [41,42], heteroarylations [43], and thioesterifications [44]. Additionally, several methods using photoredox chemistry were also published.…”
Section: Introductionmentioning
confidence: 99%